2020
DOI: 10.1111/1541-4337.12669
|View full text |Cite|
|
Sign up to set email alerts
|

Opportunities for plant‐derived enhancers for iron, zinc, and calcium bioavailability: A review

Abstract: Understanding of the mechanism of interactions between dietary elements, their salts, and complexing/binding ligands is vital to manage both deficiency and toxicity associated with essential element bioavailability. Numerous mineral ligands are found in both animal and plant foods and are known to exert bioactivity via element chelation resulting in modulation of antioxidant capacity or micobiome metabolism among other physiological outcomes. However, little is explored in the context of dietary mineral ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 338 publications
(361 reference statements)
0
27
0
Order By: Relevance
“…In general, higher values of ratio between phytic acid and essential elements were noticed in BF variant, contributing to the increased availability of essential macro-and micro-elements from poorly accessible forms [13,14,44]. It is important to emphasize that enhanced absorption of essential elements from the maize kernel during digestion could be enhanced by the increased YP concentration [18,19], what was obtained in variants without BF.…”
Section: Potential Bio-availability Of Essential Elementsmentioning
confidence: 87%
See 1 more Smart Citation
“…In general, higher values of ratio between phytic acid and essential elements were noticed in BF variant, contributing to the increased availability of essential macro-and micro-elements from poorly accessible forms [13,14,44]. It is important to emphasize that enhanced absorption of essential elements from the maize kernel during digestion could be enhanced by the increased YP concentration [18,19], what was obtained in variants without BF.…”
Section: Potential Bio-availability Of Essential Elementsmentioning
confidence: 87%
“…However, some other constituents, like vitamin C, carotenoids, amino acids, glutathione, etc. are substances that enhance the bio-availability of minerals (promoters) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, studies showed that zinc may bind to the acidic side chain of protein, phosphorylated residue, deprotonated nitrogen, and sulfur residues of amino acids and peptides. While functional groups including thiol group (cysteine, glutathione), imizadole group (hisidine), as well as asparagine and glutamine residues, phosphorylated residues, and methionine all contributed to the increased chelation capacities of zinc ( 33 ). The amino acid profiles of pumpkin seed protein and five enzymatic hydrolysates were shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5 , the zinc binding capacity of PSPHs were 64.7 ± 9.1% for PSPH-Bro, 62.5 ± 5.6% for PSPH-Alc, 57.9 ± 3.8% for PSPH-Fla, 76.3 ± 8.7% for PSPH-Pap, and 39.3 ± 3.0% for PSPH-Try, respectively. Zinc binding capacity of a certain peptide is predominately determined by the amino acid composition and arrangement of that specific peptide ( 33 ). According to the above-mentioned results, PSPH-Pap had the largest average molecular weight of 3,312 Da and contained the highest content of amino acid that tend to chelate with zinc.…”
Section: Resultsmentioning
confidence: 99%
“…Phytate to Ca molar ratios are used to predict Ca bioavailability; the phytate:Camolar ratio above 0.24 is shown to impair Ca absorption (Morris and Ellis, 1989). Food processing approaches, such as germination, fermentation, and thermal treatments, are generally seen as promising tools for increasing Ca bioavailability, as they tend to reduce the amounts of phytate and improve Ca bioaccessibility (Zhang et al, 2020b).…”
Section: Antinutrients and Bioavailabilitymentioning
confidence: 99%